2013
DOI: 10.1182/blood-2012-10-464149
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic analysis of cytarabine sensitivity in a cell-based model identifies polymorphisms associated with outcome in AML patients

Abstract: Key Points• A preclinical cell-based model identifies SNPs associated with cytarabine sensitivity that also associate with outcome in leukemia patients.• SNPs within the MCC gene were associated with cytarabine sensitivity in lymphoblastoid cell lines and leukemic blasts from patients.A whole-genome approach was used to investigate the genetic determinants of cytarabineinduced cytotoxicity. We performed a meta-analysis of genome-wide association studies involving 523 lymphoblastoid cell lines (LCLs) from indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 43 publications
(52 reference statements)
1
35
0
Order By: Relevance
“…It is estimated that approximately 33.6 in every 1, 000, 000 children under 15 years old will develop ALL. While acute myeloid leukemia (AML) is the most common form of acute leukemia in adults as well as in children (Gamazon et al, 2013), it causing immature myeloid precursors to accumulate, and resulting in an estimated 13, 330 cases and an estimated 8, 950 deaths in the United States in 2010 (Wang et al, 2013). But unfortunately, the exact pathological mechanism of leukemia is still unclear recently.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 33.6 in every 1, 000, 000 children under 15 years old will develop ALL. While acute myeloid leukemia (AML) is the most common form of acute leukemia in adults as well as in children (Gamazon et al, 2013), it causing immature myeloid precursors to accumulate, and resulting in an estimated 13, 330 cases and an estimated 8, 950 deaths in the United States in 2010 (Wang et al, 2013). But unfortunately, the exact pathological mechanism of leukemia is still unclear recently.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations, particularly SNPs, have been identified in these genes involved in Ara-C transport and metabolism [25][26][27]. Both in vivo and in vitro studies demonstrated that the activities of these enzymes are correlated with polymorphic gene variations [28,29], and some of these SNPs are even highly correlated with treatment response and survival of AML patients with Ara-C based chemotherapy [30][31][32][33]. Previous study found that rs329491 of SLC29A1 maybe a favorable survival factor for patients with pancreatic cancer [34].…”
Section: Introductionmentioning
confidence: 99%
“…In liver cancer, MCC expression is lost through LINE‐1 retrotransposition events or microRNA targeting . Furthermore, SNPs within the MCC gene and its expression levels are associated with responsiveness to chemotherapy treatment in acute myeloid leukaemia . Limited data are available for other cancer types, except for lung cancer where expression of MCC is also variable but promoter methylation is rare …”
mentioning
confidence: 99%